Development and usage of computer expert systems in agriculture : the case example for service and maintenance of agricultural tractors - Bardaie, Mohd Zohadie; N., Kumarason (1988)
An expert system is a computer software system that is able to provide advice in particular subject area equal in quality to that which could be provided by an acknowledged human expert. Typically, an expert system is based on an extensive body of knowledge about a specific problem area. In general, this knowledge will be organized as a collection of rules that allow the system to draw conclusions from given data or premises, thereby letting it offer intelligent advice or take intelligent decisions. Thus, expert systems do best when there is a well defined area of knowledge and in situations where it is possible to draw clear conclusions or recommendations. So far, applications in agriculture have been dominated by crop pest and disease management. These seems every likelihood that many more apllication will appear. The current and potential usage of expert system in agriculture is discussed in the paper, along with a presentation of the case for the service and maintenance of agriculture tractors. A brief discussion on expert system structure is also presented in the paper.